PENGARUH KUALITAS PRODUK, HARGA, PROMOSI DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN MINUMAN ISOTONIK (Studi Pada Konsumen Minuman Isotonik di Kota Semarang) - Nia Safitri Dewi, 11.05.51.0062; Eddy Prabowo, Rokh (Students Journal of Economic and Management, 2018)
This study aims to analyze the influence of Product Quality, Price, Promotion and Lifestyle to Purchase Decision isotonic drinks on consumer isotonic drinks in Semarang City. With the population of all consumers of isotonic drinks in Semarang City. The sample is set as many as 100 people with the criteria (purposive sampling) of consumers who buy isotonic drinks and those located in Semarang City. Primary data were obtained by closed questionnaire, because the respondent only crossed the selected number from one to five (likert scale), while secondary data was obtained by library. Based on the validity test all the indicators declared valid and based on reliable reliability test. Model test using F (Goodness of Fit) test and Adjusted R2 test (coefficient of determination), hypothesis test using t test with standard beta coefficient and significance level <0.05. Based on the model test the adjusted value of R2 is 0.720 and the F value is 64.493 with the sig value 0.000. Based on the results of hypothesis testing then: The quality of the product has a significance value of 0.000 <0.05 and standard beta coefficient of 0.659, so that product quality has a positive and significant effect on purchasing decisions of isotonic drinks. Price has a significance value of 0.001 <0.05 and a standard beta coefficient value of 0.19, so the price has a significant positive effect on the purchase decision of isotonic drinks. The promotion has a significance value of 0.014 <0.05 and a standard beta coefficient value of 0.137, so the promotion has a positive and significant effect on purchasing decisions of isotonic beverages and Lifestyle has a significance value of 0.000 <0.05 and a standard beta coefficient value of 0.245, so the lifestyle has a positive and significant effect on purchasing decisions of isotonic drinks.Keywords: product quality, price, promotion, lifestyle, purchasing decision